Special Issue “Analysis and Experimental Study on Natural Gas Hydrate Exploitation Processes” - Castellani, Beatrice; Nicolini, Andrea (Processes, 2023)
This is an Editorial paper of the Special Issue “Analysis and Experimental Study on Natural Gas Hydrate Exploitation Processes”, published on Processes, MDPI. The authors are also the guest editors. Natural gas hydrates are considered a huge reservoir of methane, with the amount of stored organic carbon twice the amount contained in all currently recoverable worldwide conventional hydrocarbon resources. Research outcomes from theoretical studies, molecular modeling, and experimental works on the recovery of gas from hydrate in laboratory settings have revealed the possibility of energy production from hydrate resources. Traditional production methods include depressurization, thermal stimulation, in-situ combustion, and chemical injection. In addition, a novel technique based on carbon dioxide injection into methane hydrate, has been proposed to recover methane and simultaneously store carbon dioxide, enhancing the idea of a carbon neutral fuel source. Nevertheless, several issues need further investigation, for instance, kinetic and thermodynamic aspects, hydrates’ mechanical properties as well as full-scale exploitation processes and related energy and environmental analysis. This Special Issue “Analysis and Experimental Study on Natural Gas Hydrate Exploitation Processes” will collect new outcomes on the above-mentioned issues and offer the scientific community an opportunity to illustrate their research.